PENGEMBANGAN SKENARIO PEMBELAJARAN BERBASIS PBL DAN HOTS TEKS DRAMA - Desti Setia Herawati; Mulyanto Widodo; Khoerotun Nisa Liswati (FKIP Universitas Lampung, 2020)
The problem in this research is how the development of a learning scenario based on problem based learning and higher order thinking skills in drama text for SMP class VIII. The purpose of this study is to describe the development of a learning scenario based on problem based learning and higher order thinking skills in drama text for SMP class VIII. This research uses research and development (rnd) method. The result of this study is the creation of a learning scenario product in drama text for SMP class VIII that has been validated. Validation is conducted by expert lecturers to test the feasibility of the product. The result of the validation is from material experts on the learning aspect obtained an average percentage of 89.9%, and the content aspect obtained an average percentage of 89.9% with very decent criteria. Masalah dalam penelitian ini adalah bagaimana pengembangan skenario pembelajaran berbasis problem based learning dan higher order thinking skills teks drama kelas VIII SMP. Tujuan penelitian ini untuk mendeskripsikan pengembangan skenario pembelajaran berbasis problem based learning dan higher order thinking skills teks drama kelas VIII SMP. Penelitian ini menggunakan metode research and development (rnd). Hasil penelitian ini ialah terciptanya produk skenario pembelajaran pada teks drama kelas VIII SMP yang sudah divalidasi. Validasi dilakukan oleh dosen ahli untuk menguji kelayakan produk. Hasil validasi dari ahli materi pada aspek pembelajaran diperoleh rata-rata persentase 89,9%, dan pada aspek isi diperoleh rata-rata persentase 89,9% dengan kriteria sangat layak. Keywords: scenario development, PBL, HOTS, drama text.